Ensino das ciências ambientais a partir das tecnologias culturais no município de Coari – AM - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
Biotechnology is present in various sectors of society, however, it is still very distant from the daily life of the school space. It is understood that the analysis of biotechnological phenomena present in local cultural technologies can bring the approach practiced in school closer to the reality experienced by students. In this sense, the present study sought to develop a notebook with interdisciplinary activities specifically for the Integrated Technical Course in Agriculture and Cattle Raising of IFAM/Coari, so that it contributes significantly to the teaching of Environmental Sciences and that dialogues with the reality of the students. With this purpose, the research aimed to evaluate from the perception of educators and the relevance of contextualizing the teaching of biotechnology from Local Cultural Technologies as a generating theme for interdisciplinary activities. For this, it was necessary to "identify, from the perception of educators of the Integrated Technical Course of Agricultural Science and Technology of IFAM-Coari, biotechnological products and processes expressed in local cultural technologies", "analyze the Pedagogical Project of the Integrated Course of Agricultural Science and Technology the curriculum structure and the possibilities of establishing interdisciplinary activities with Local Cultural Technologies as the generating theme", in addition to developing the notebook of interdisciplinary activities that favor the contextualization of biotechnology teaching from Local Cultural Technologies. The research had a qualitative and descriptive approach, which was organized from the standpoint of Systemic Complexity. A structured questionnaire was used in the Google Forms tool and the data analysis was not probabilistic. The strategic procedures were developed in three steps: i) Bibliographic research, ii) Documentary research and iii) Field research. From the results it was possible to develop the educational product "Interdisciplinary Activity Booklet for the teaching of Environmental Sciences from the Cultural Technologies in the municipality of Coari-Am", guided by the PPC of the course and under the guidance of BNCC in a contextualized and integrative way. In this sense, the educators agreed with the importance of contextualization of knowledge as a teaching strategy and identified the relevance of the dialogue between the local knowledge expressed in cultural technologies and the curriculum content established in the Pedagogical Project of the course where they teach.
Keywords: Biotecnologia - Estudo e ensino; Abordagem interdisciplinar do conhecimento na educação; Professores de ensino técnico - Coari (AM); CIENCIAS BIOLOGICAS; OUTROS: CIENCIAS; Processos biotecnológicos; Educação; Ensino contextualizado; Cultura local; Biotechnological processes; Education; Contextualized teaching; Local culture